Dosimetric comparison of three dimensional computer tomography planned radiotheraphy versus conventional techniques for left sided breast cancer - Wong, Sharon Mei Mei. (2008)
Research study on the dose homogeneity and isodose distribution patterns between 3D CT planned techniques versus conventional two dimensional (2D) radiotherapy was conducted, particularly in Asian women.